Quantum computation for periodic solids in second quantization - Aleksei V. Ivanov; Christoph Sünderhauf; Nicole Holzmann; Tom Ellaby; Rachel N. Kerber; Glenn Jones; Joan Camps (Physical Review Research, 2023)
In this work, we present a quantum algorithm for ground-state energy calculations of periodic solids on error-corrected quantum computers. The algorithm is based on the sparse qubitization approach in second quantization and developed for Bloch and Wannier basis sets. We show that Wannier functions require less computational resources with respect to Bloch functions because (i) the L_{1} norm of the Hamiltonian is considerably lower and (ii) the translational symmetry of Wannier functions can be exploited in order to reduce the amount of classical data that must be loaded into the quantum computer. The resource requirements of the quantum algorithm are estimated for periodic solids such as NiO and PdO. These transition metal oxides are industrially relevant for their catalytic properties. We find that ground-state energy estimation of Hamiltonians approximated using 200–900 spin orbitals requires ca. 10^{10}–10^{12} T gates and up to 3×10^{8} physical qubits for a physical error rate of 0.1%.